"Modified tongue-in-groove": a new tip-plasty technique and comparison of its effect on correction of the nasolabial angle with the columellar strut technique. Issue 5 (June 2020) - Delarestaghi, M.M.; Jahandideh, H.; Sanaei, A.; Jan, D.
Abstract: Ptosis of the nasal tip is one of the most challenging aspects of rhinoplasty, and the tongue-in-groove (TIG) and the columellar strut (CST) techniques are the two most common procedures used to improve it. The purpose of this study was to introduce a new modification of TIG, to evaluate the long term results of the modified TIG, and to compare its effect on correction of the nasolabial angle with that of the CST. Eighty patients with droopy nasal tips (all female, aged <40 years) were divided into two groups of 40 each according to the technique used for correction (modified TIG or CST). The nasolabial angle was recorded preoperatively, immediately postoperatively, and after one year. The mean was 90.80° in the modified TIG group and 94.87° in the CST preoperatively, which did not differ significantly (p = 0.056). Immediately postoperatively, it was significantly higher in the CST group (116.92° compared with 107.10°, p = 0.01), but at the one-year follow-up, the droop was similar in both groups (−7.35° in the modified TIG, and −7.48° in the CST group, respectively, p = 0.942). Both techniques significantly increased the nasolabial angle postoperatively (p < 0.001 in both cases). This study showed that the modified TIG is a reliable and effective technique for reconstructing and correcting a droopy nasal tip, and its long-term efficacy is comparable with that of CST.